In Memoriam Marlos Nobre (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The text pays tribute to the career of Brazilian composer Marlos Nobre (1939-2024), through his contribution to Latin American academic music. Different aspects in which his work stood out, his formation and international consolidation are examined. The syncretism between the avantgarde of the 20th century and traditional Brazilian rhythms is highlighted. An analytical musicological approach is adopted, based on documentary review and critical analysis of Nobre's compositional production. Relevant bibliographical sources are contrasted with the analysis of his music, which was divided into five stylistic periods by the composer. The relationship of his work with the sociocultural context, his influence on Latin American music and his role as a cultural manager are examined. It is shown that Marlos Nobre's work is characterized by the integration of traditional Brazilian rhythms, such as frevo, forró, maracatú, It is expressed that there was a compositional transformation from nationalism to an aesthetic of its own, balanced between the academic and the popular. among others, with avantgarde techniques such as polytonality, atonalism and timbre exploration. It is concluded that Nobre left a work with its own identity, comparable in importance to that of VillaLobos and Ginastera, being an essential reference in the music of the 20th and 21st century.
Keywords: Marlos Nobre; Latin American composers; composers from Brazil; contemporary Latin American music